Spatial development initiatives – potentials, challenges and policy lessons: with a specific outlook for inclusive agrocorridors in Sub-Sahara Africa - Caroline Reeg (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
The promotion of agrocorridors has gained increasing attention in discussions on attracting investments, stimulating agribusiness development, and addressing food insecurities and malnutrition in sub-Saharan Africa. Though agrocorridors are being widely talked about, very little empirical data exists on the economic performance and inclusiveness of agricultural corridor initiatives. Especially in sub-Saharan Africa, only a few, if any, implemented cases of integrated agrocorridors can be found. However, although agrocorridors constitute a new instrument to shape spatial economic development, other spatial development initiatives (SDIs) exist – that is, spatially-organised economic development schemes with the aim to develop business and investment environments in specific areas – that have longer track records. This report shows that SDIs are very difficult to get right. Several necessary but no sufficient conditions exist for success. Though the “island” approach of SDIs promises to address and remove various growth obstacles, evidence suggests that spatial approaches rarely deliver a considerably improved environment beyond what is available “outside” of a targeted area. Overall, it is shown that the economic and social performance of SDIs is inherently linked to the quality of the national investment climate.
Keywords: 330; Landwirtschaft und ländliche Entwicklung